(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and Purpose: according to the studies that have been conducted so far, the corona virus has more severe clinical consequences in diabetic patients than in non-diabetic cases; Therefore, the present study was conducted with the aim of investigating the severity of the disease and mortality in patients infected with the Coronavirus between these 2 groups. Materials and Methods: In this cross-sectional-analytical study, the clinical records of 185 hospitalized patients with a positive laboratory diagnosis of Covid-19 were reviewed from February 14 to February 26, 2020. The patients were divided into 2 non-diabetic (95 people) and diabetic (90 people) groups, and their clinical symptoms and blood biochemical parameters were compared. Results: Based on the results, most of the patients were male and compared to non-diabetic patients, the diabetic group was significantly older (P=0.01). In this study, the disturbance in paraclinical factors such as d-dimer, BUN, VBG and lymphopenia in diabetic patients was significantly higher than in the control group, which indicates the need for more care in diabetic patients. Conclusion: it is suggested to follow health protocols for people with land diseases, be more careful., therefore, more extensive research with larger sample sizes is needed to achieve more accurate results.